High-performance alpha-voltaic cell based on a 4H-SiC PIN junction diode. (15th January 2022) - Gao, Runlong; Liu, Linyue; Li, Yang; Shen, Lvkang; Wan, Pengying; Ouyang, Xiao; Zhang, Haozhe; Ruan, Jinlu; Zhou, Leidang; Chen, Liang; Zhang, Xianpeng; Liu, Jinliang; et al.
Highlights: High-performance and long-life alpha-voltaic cell based on SiC diode was fabricated. The AV cell achieved excellent PCE of 0.88%, with a strikingly high Voc of 1.99 V. Main factors that influence the performance of AV cell have been analyzed in depth. Abstract: Alpha-voltaic cells have great potential in military, biomedical, and infrastructure applications due to their characteristics of long operating life, small volume, and superior adaptability. However, improvements in power conversion efficiency (PCE), and the balance between power density and stability have been a challenge owing to the 'poor-matching' between energy conversion transducers and alpha-emitting isotope sources, as well as the radiation damage to semiconductor devices. In this study, we report the electrical properties of a high-performance alpha-voltaic cell based on a 4H-SiC PIN junction diode energy conversion transducer (active area of 1 cm 2 ) that has been experimentally validated by a He ions electrostatic accelerator. Remarkably, the alpha-voltaic cell displayed an excellent PCE of 0.88%, exhibiting a nearly 7-fold enhancement compared to alpha-voltaic cells of previous studies, with a strikingly high open-circuit voltage of 1.99 V, a short-circuit current of 13.64 nA/cm 2, and a maximum output power density of 16.78 nW/cm 2 .